Navigating NPLs: Financial Health Analysis of BPR Bank Gresik - Ramadhanti Dwi Novitasari; Anita Handayani (INNOVATION RESEARCH JOURNAL, 2023)
The Regional Public Bank (BPR) Bank Gresik plays a crucial role in supporting small businesses in rural communities and economically vulnerable groups in urban areas through the provision of credit loans. Credit, as the primary productive asset, serves as the main source of income for the bank. However, credit disbursement also entails credit risk, which can lead to the occurrence of non-performing loans. This research aims to identify the handling of non-performing loans and its impact on profit growth at Bank Gresik. The research methodology employed is descriptive with a qualitative approach. Data analysis is conducted using the Miles and Huberman model, involving data collection, data reduction, data presentation, and drawing conclusions. The results of the research indicate that the causes of non-performing loans originate from both internal and external factors of the bank. The handling of non-performing loans involves various steps, including telephone warnings, direct home collections, warning letters, summon letters, restructuring, posting banners on collateral, cession, simple lawsuits, insurance disbursement, and the takeover of debtor collateral. Despite the increase in the non-performing loan rate, the bank's profit continues to grow due to the influence of interest rates..